The Effect of Arabic on EFL Students’ Writing - Hamar, Fatima (My University, 2017)
This study focuses on language interference by means of studying how English writing is affected by Arabic language with a special attention is paid to the major errors made by EFL learners. The investigation is divided into three chapters, the first has provided an overview about language interference and language transfer, the second one is practical part in which we have used two instruments: a questionnaire and a test as we have analyzed the data collected. Whereas, in the third chapter, we attempt to give some recommendations and suggested solutions to be adapted by both teachers and students in order to avoid the negative transfer errors. Thus, results show that Arabic affect students when writing English to some extent, as they commit mistakes in vocabulary (word choice), grammar (tenses), and even punctuation.
The case of third year LMD students at Mostaganem University
Keywords: Linguistic Interference; English Writin; EFL Classroom